一、 因式分解 (m^2-n)^2-(2n-)m^2 (a+2)^2-2a(a+2) (a^2+1)^2-4a^2 -a^4+2a^2b^2-4b^4 二、计算-3^2+(1/3)^-3+(π-9)^0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 09:40:00
一、因式分解(m^2-n)^2-(2n-)m^2(a+2)^2-2a(a+2)(a^2+1)^2-4a^2-a^4+2a^2b^2-4b^4二、计算-3^2+(1/3)^-3+(π-9)^0一、因式分
一、 因式分解 (m^2-n)^2-(2n-)m^2 (a+2)^2-2a(a+2) (a^2+1)^2-4a^2 -a^4+2a^2b^2-4b^4 二、计算-3^2+(1/3)^-3+(π-9)^0
一、 因式分解 (m^2-n)^2-(2n-)m^2 (a+2)^2-2a(a+2) (a^2+1)^2-4a^2 -a^4+2a^2b^2-4b^4 二、计算-3^2+(1/3)^-3+(π-9)^0
一、 因式分解 (m^2-n)^2-(2n-)m^2 (a+2)^2-2a(a+2) (a^2+1)^2-4a^2 -a^4+2a^2b^2-4b^4 二、计算-3^2+(1/3)^-3+(π-9)^0
一、因式分解
(m^2-n)^2-(2n-)m^2?
(a+2)^2-2a(a+2)
=a^2+4a+4-2a^2-4a
=4-a^2
=(2+a)(2-a)
(a^2+1)^2-4a^2
=(a^2+1)^2-(2a)^2
=(a^2+1+2a)(a^2+1-2a)
=(a+1)^2(a-1)^2
-a^4+2a^2b^2-4b^4
=-(a^4-2a^2b^2+4b^4)
=-(a^2-b^2)^2
=-(a+b)^2(a-b)^2
二、计算-3^2+(1/3)^-3+(π-9)^0
=-9+27-3+1
=16
因式分解(m-n)^2-(m+n)^2
(m-n)(m-n+2)-8因式分解
因式分解m^2-n^+m-n
因式分解m^2-(n+1)m+n
因式分解(m-n)^2-1
因式分解(m-n)^2-(n-m)(m 2n)
m^2(m-n)+n^2(n-m)因式分解
因式分解(n-m)^3(m-n)^2-(m-n)^5
因式分解4m^2(m-n)+4n(n-m)
因式分解 4n^2-(m+n)^2
-(m+n)^2+n^2因式分解 求教
4m^2-(m+n)^2因式分解
m^3n^2-m^5 因式分解
(m-n)*2+2n(n-m)*2的因式分解
(m-n)*3+2n(n-m)*2的因式分解
因式分解 (m-n)³+2n(n-m)²
因式分解一题.9(m+n)^2-4(m-n)^2
(m-n)+2n(m-n)(m-n)的平方+2n(m-n)因式分解